Dolutegravir resistance mutations: lessons from monotherapy studies. Issue 3 (June 2018) - Blanco, José L.; Marcelin, Anne-Geneviéve; Katlama, Christine; Martinez, Esteban
Abstract : Purpose of review: Dolutegravir (DTG) is a second-generation integrase strand transfer inhibitor (InSTI) with an outstanding antiviral potency, good tolerability, good pharmacokinetic profile with a lack of major drug–drug interactions, and a barrier to resistance higher than the other compounds of the class (raltegravir and elvitegravir) and allegedly as high as that of boosted protease inhibitors. For these reasons, DTG, after successful results in a context of triple therapy in various clinical scenarios, has been investigated mostly by independent investigators in less-drug regimens, including dolutegravir monotherapy, in the context of a growing clinical interest for adjusting successful antiretroviral therapy to the increasing number of limitations for standard antiretroviral therapy in some HIV-infected patients. However, the development of genotypic resistance in case of failure to DTG monotherapy was unexpected. Recent findings: Data on efficacy and resistance from preclinical studies, randomized clinical trials and clinical cohorts of HIV-infected patients treated with DTG monotherapy published in indexed journals or presented at international meetings were reviewed. Summary: Monotherapy with dolutegravir has a high rate for resistance selection in the integrase gene through different pathways in case of virological failure.